Lithological distribution using band ratio technique in Southern Langkawi, Kedah, Malaysia - Du, Yaokai; Teoh, Ying Jia; Ahmad Abir, Ismail; Putra Jaya, Ramadhansyah; Ulfa, Yuniarti (Springer, 2025)
Remote sensing techniques provide valuable insights into lithological interpretation and improve the accuracy of geological surveys. Due to the complex terrain of Langkawi Island, which is in the northwestern part of the Malay Peninsula, conducting detailed field investigations is challenging. However, advancements in technology have made remote sensing an effective method for surveying areas that are hard to access. In this study, Landsat 9 data, with a spatial resolution of 30 m, served as the primary source of information. The initial preprocessing of this data was done using ENVI software. After preprocessing, carefully selected band combinations and ratios were used to extract valuable geological insights. Remote sensing-based lithological interpretation is crucial in modern geological surveys. In this study, the band ratio technique was employed to map the lithological distribution. This study focused on the southern end of the Langkawi archipelago, specifically the Dayang Bunting and Tuba Islands, where the geological characteristics are of particular interest due to their unique geological history and topography. To achieve the objectives, the band ratio technique applied to satellite imagery allows for the derivation and analysis of the lithological distribution patterns on these islands. This study compared previously used band ratio combinations with those tested here to find the most effective for distinguishing lithology types. After testing 32 permutations, by comparing with the original geological map and combining previous field observations, the four most successful combinations were visually evaluated: RGB 2/3 2/5 2/6, 4/3 4/6 4/7, 2/4 2/6 2/7, and 5/2 5/6 5/7. On Dayang Bunting and Tuba Islands, these combinations revealed distinct colors, differentiating limestone, marble, and granite. This study enhances the understanding of lithological composition in Dayang Bunting and Tuba Islands and demonstrates the effectiveness of band ratio techniques for geological surveys in similar regions. However, challenges such as varying image quality, atmospheric conditions, and the need for local calibration may arise when applying this method in other settings, which should be considered for broader adoption.